Factors and Strategy for Sustainable Tourism in Boti Village, East Nusa Tenggara - Simon Suddin (Program Pascasarjana, 2018)
The potentiality and limitation of tourism development in Boti Village of Timor Island lead to the needs of a comprehensive strategy to enhance the sustainability of tourism. The aims of the research are to describes the variable influence the sustainability of tourism and drawn the design for sustainable tourism in Boti Village. This research identifies 13 variables as crucial factors to determine the sustainable tourism in Boti Village. It is including strengtheningÂ local law in Boti, implementation of tourism regulation, formalizing regulation related to tourism zonation, strengthening conservation program, infrastructure development, accessibility improvement, fundraising and generating public support for funding, strengthening community development program and implementation, promoting research for tourism development, strengthening role of local institution (or locally called Lembaga Adat/Masyarakat), strengthening role of government in tourism infrastructure and accessibility development, strengthening the role of private sector,Â and developing and improving proper marketing strategy.Keywords: conservation, responsible tourism, sustainable tourism.